Kisspeptin as a potential biomarker throughout pregnancy. (September 2019) - Hu, Kai-Lun; Zhao, Hongcui; Yu, Yang; Li, Rong
Abstract: Kisspeptins are a family of neuropeptides that are critical for the puberty initiation and female fertility. Plasma or serum kisspeptin is mainly derived from the placenta during pregnancy and plasma kisspeptin levels significantly increase across pregnancy. Plasma kisspeptin levels could be used as a potential biomarker for the detection of miscarriage, pre-eclampsia, gestational trophoblastic neoplasia (GTN), and fetal development. Kisspeptin may also be involved in the process of parturition by stimulating oxytocin secretion during term pregnancy. This review discussed the potential use of kisspeptin as a marker across pregnancy and highlighted the unresolved problems in this area. Tweetable abstract: Plasma kisspeptin levels could be used as a potential biomarker across pregnancy.